Ethnomedicinal Study of Plants Used in Phytotherapeutics among Indigenous Communities of District Bhimber, Azad Kashmir and Migrants to United Kingdom: Ethnomedicinal Study of Plants used in Phytotherapeutics - Maqbool, Mehwish; Ajaib, Muhammad; Ishtiaq, Muhammad; Azam, Shehzad; Hussain, Tanveer (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The key purpose of current study was to investigate impact of foreign culture of Britain on traditional herbal medicines on inhabitants and migrants of District Bhimber of Azad Jammu and Kashmir, Pakistan. The current ethnomedicinal (EMs) study was conducted by using questionnaire methodology using structured and semi-structured interview protocols involving 72 interviewees of both genders and age range of 30-100 years. The collected data was analyzed by Informant Consensus Factor (ICF), family index (Fi), fidelity level (FL), data matrix ranking (DMR), Use mode in %age and priority ranking (PR) analyses tools. In this research, total 50 medicinal plants (MPs) were documented as traditional ethnomedicines (TEMs). Euphorbiaceae had highest plant taxa (10) being used as EMs. Leaf was most commonly (21%) used part of plant in TEMs while decoction (32) ranked first in use form. Highest ICF was found for asthma (0.90) and highest FL was shown by Otostegia limbata (95 %). DMR showed Acacia modesta at 1st rank for its multiple usages. PR depicted “use of plants for construction” number first (1st) as key biotic threat for medicinal plants (MPs). The analysis depicted that the people purchase and fetch TEMs from their native hometown (Jatlan) or buy from British botanic markets. The study proves that immigrants now living in UK hitherto use TEMs for cure of ailments as complimentary alternative medicines (CAMs). There is less information of TEMs reported by migrants of Bhimber in Western (UK) pharmacological databases and this demand to do further detailed work on ethnopharmacological analysis for rationale use within safety limits and avoid any toxicity implications. Furthermore, young generations of migrants have least interest in CAMs and there is fear of loss of knowledge of MPs of Azad Jammu and Kashmir which demands dire need to document the TEMs data for conservation of cultural and biological diversity of the area.